Approximation common fixed point of asymptotically quasi-nonexpansive-type mappings by the finite steps iterative sequences - Xian Jun Long; Shih-Sen Chang; Jing Quan (Fixed Point Theory and Applications, 2006)
The purpose of this paper is to study sufficient and necessary conditions for finite-step iterative sequences with mean errors for a finite family of asymptotically quasi-nonexpansive and type mappings in Banach spaces to converge to a common fixed point. The results presented in this paper improve and extend the recent ones announced by Ghost-Debnath, Liu, Xu and Noor, Chang, Shahzad et al., Shahzad and Udomene, Chidume et al., and all the others.